Postmodernizm ku pokrzepieniu serc albo anty-antytupia Ołeksandra Irwancia - Kupidura, Ryszard (Studia Ukrainica Posnaniensia, 2025)
The paper analyzes the generic and ideological evolution of the works of Oleksandr Irvanets, one of the leading representatives of Ukrainian postmodernism, from dystopia to the concept of the anti-dystopia. In the first part, the author reconstructs the context of the literary group “Bu-Ba-Bu” and outlines its significance for shaping post-totalitarian Ukrainian culture. The next section examines Irvanets’s dystopian trilogy (Rivne/Rovno, Ochamymria, Libenkraft’s Disease), interpreted as an artistic response to the remnants of the Soviet system and the anxieties of the first decades of independence. The following part considers the novel Kharkiv 1938 as an example of an alternative history. Thus, this generic transformation is read in the light of Przemysław Czapliński’s concept as an attempt to overcome dystopian fatalism.